Renewable palm oil sticks biomass‐derived unique hierarchical porous carbon nanostructure as sustainability electrode for symmetrical supercapacitor. Issue 1 (13th September 2022) - Julnaidi,; Saputra, Edy; Nofrizal,; Taer, Erman
Abstract: BACKGROUND: Three‐dimensional and hierarchical porous materials enriched with 2D nanostructure can boost the electrochemical performance of carbon‐based electrodes in the supercapacitor devices. These materials are obtained from novel precursors of palm oil stock biomass. The unique combination of hierarchical and 2D nanostructures was controlled using ZnCl2 impregnation of 0.3–0.9 mol L −1 with high‐temperature pyrolysis. RESULTS: Impregnation with 0.5 mol L −1 ZnCl2 (POSC5) produced the highest specific surface area with dominant micropores of 89% in a total volume of 0.343 cm 3  g −1 . POSC5 was shown to have an excellent morphological combination of trimodal‐foam‐sponge‐like hierarchical porosity with large messy short 2D nano‐rod structures as the optimum carbon preparation. A symmetrical system was designed as a solid electrode without a binder, confirming high capacitive properties of 256 F g −1 in 1 mol L −1 H2 SO4 electrolyte with capacitance retention of 76% at 10 mV s −1 . The results showed that the transport and resistance behavior of the charge tends to be stable and satisfactory at an internal resistance of 0.012 Ω, with the energy density increased from 9.14 to 21.19 W h kg −1 at 1 A g −1 in 1 mV s −1 . CONCLUSION: Therefore, this research provides an environmentally benign and novel approach for developing a high‐quality, sustainable biomass carbon‐based electrode material for electrochemical energy storage applications. © 2022 Society of Chemical Industry (SCI).